2008
DOI: 10.1038/nature06823
|View full text |Cite
|
Sign up to set email alerts
|

The presence of methane in the atmosphere of an extrasolar planet

Abstract: Molecules present in the atmospheres of extrasolar planets are expected to influence strongly the balance of atmospheric radiation, to trace dynamical and chemical processes, and to indicate the presence of disequilibrium effects. As molecules have the potential to reveal atmospheric conditions and chemistry, searching for them is a high priority. The rotational-vibrational transition bands of water, carbon monoxide and methane are anticipated to be the primary sources of non-continuum opacity in hot-Jupiter p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
569
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 559 publications
(597 citation statements)
references
References 22 publications
19
569
2
Order By: Relevance
“…In the recent paper by Gibson, Pont & Aigrain (2010;hereafter GPA10), the authors reanalyzed transmission spectroscopic measurements of HD 189733b (Swain, Vasisht & Tinetti 2008; hereafter SVT08), and XO-1b (Tinetti et al 2010) and find that they cannot reliably reproduce the previous results. Here we explore the differences in method that lead the two teams to such different conclusions.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…In the recent paper by Gibson, Pont & Aigrain (2010;hereafter GPA10), the authors reanalyzed transmission spectroscopic measurements of HD 189733b (Swain, Vasisht & Tinetti 2008; hereafter SVT08), and XO-1b (Tinetti et al 2010) and find that they cannot reliably reproduce the previous results. Here we explore the differences in method that lead the two teams to such different conclusions.…”
Section: Introductionmentioning
confidence: 64%
“…Measurements with the NICMOS instrument on the Hubble space telescope demonstrated that molecular spectroscopy of exoplanet atmospheres was possible and provided the first detection of methane in a planet orbiting another star (Swain et al 2008). From this initial result, molecular spectroscopy of exoplanet atmospheres has grown rapidly, using Spitzer (Grillmair et al 2008), Hubble (Swain et al 2009a(Swain et al , 2009b, and ground-based measurements Thatte et al 2010;Snellen et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The similarities between the phase curves at 8 and 24 μm suggests that either both wavelengths sense similar atmospheric pressures or that the circulation behaves in a fundamentally similar fashion across the relatively modest (factor of 2 − 3) range in pressures that are sensed here according to atmosphere models. The uncertain abundance of methane in the planet's atmosphere complicates this picture (Swain et al 2008), but based on other data we can definitively rule out the presence of an opaque cloud layer above the range of the 8 and 24 μm contribution functions that, if present, might affect these observations (Charbonneau et al 2008, Barman 2008.…”
Section: μM Phase Curve For Hd 189733bmentioning
confidence: 99%
“…In the case of HD 189733b, this method recently yielded the detection of water (Tinetti et al 2007), methane (Swain et al 2008), and the likely presence of small-particle clouds or hazes (Pont et al 2008). The technique of secondary eclipse observations at infrared wavelengths (Charbonneau et al 2005;Deming et al 2005; sometimes referred to as occultation spectroscopy) has borne tremendous fruit owing to the remarkable stability of the Spitzer Space Telescope (resulting in part from its heliocentric orbit).…”
Section: Constraints On Exoplanet Physical Structures and Atmospheresmentioning
confidence: 99%